2010
DOI: 10.1086/652870
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological Studies ofLeishmania amazonensisInfection in Resistant and in Susceptible Mice

Abstract: Leishmania amazonensis infection was studied in mice to evaluate the evolution of leishmaniasis. The association of different methods, such as lesion kinetics, limiting dilution analysis, and immunohistochemistry, established different levels of susceptibility and resistance. Mice were arranged in 3 groups: susceptible (C57BL/10 and CBA), relatively resistant (DBA/2), and resistant (C3H.He). The histopathological analysis of primary lesions and draining lymph nodes showed a predominance of eosinophils and mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 44 publications
2
40
1
Order By: Relevance
“…For the assessment of long-term immunity, mice received the same immunization protocol but were challenged 1 month after the last vaccine dose. In these animals, cross-protection was evaluated by monitoring the sizes of footpad lesions and by determination of the parasite load in lesions after euthanasia by a limiting dilution assay as modified from de Oliveira Cardoso et al (36). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the assessment of long-term immunity, mice received the same immunization protocol but were challenged 1 month after the last vaccine dose. In these animals, cross-protection was evaluated by monitoring the sizes of footpad lesions and by determination of the parasite load in lesions after euthanasia by a limiting dilution assay as modified from de Oliveira Cardoso et al (36). …”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of depletion treatment was monitored by the increase of the size of footpad lesions along the 6 weeks of experiment. In addition, the parasite load in lesions on week 6 was evaluated by a limiting dilution assay (36). …”
Section: Methodsmentioning
confidence: 99%
“…amazonensis infection is not limited to the skin. The parasite tends to disseminate to the lymph nodes and can even reach the spleen and liver [23]. The cytokines measured in sera revealed an enhancement of IL-4 and IL-10 caused by L .…”
Section: Discussionmentioning
confidence: 99%
“…protozoa. In vitro, eosinophils are chemoattracted toward L. amazonensis promastigotes, and in vivo studies have demonstrated eosinophil recruitment to the infection site of L. amazonenesis and L. major [50, 51]. During the initial hours of L. mexicana infection, eosinophils have been observed close to degranulating mast cells at the site of parasite inoculation, suggesting a role in parasite clearance [52].…”
Section: Eosinophilsmentioning
confidence: 99%
“…A contribution of eosinophils during leishmaniasis has recently been examined in more detail by de Oliveira et al [50]. This group showed that infection with L. amazonensis causes an eosinophil-rich infiltrate in primary lesions and draining lymph nodes.…”
Section: Eosinophilsmentioning
confidence: 99%